Uma contribuição ao estudo dos móveis de madeira e seus derivados - Ramos, Lúcia Flávia Milani Dias (2013)
The furniture made of wood or wood-based is present in various stages of the human life. Although it is a relevant and current issue that has being used constantly and the use of wood and wood-based has increased as raw material in furniture manufacture, literature that addresses the topic is incomplete and scarce. The aim of this research was to gather into a single text a larger amount of information about the subject, covering studies on: the history of furniture in way to know its origins and transformations due to the technical and aesthetic sensibility of its designer and maker; types of wood and of wood-based that can be used in the furniture manufacturing; specific standards related to minimum and maximum dimensions and that regulate furniture sector; ergonomic measures; accessories used in the final process of furniture composition; connections used for fixing; components used for finishing; design effects and the sector trends. All the work was compiled from a variety of theoretical references, without being guided from a specific author. It is expected that this academic study is relevant to society in general, and especially to the furniture industry and to the wood industry, becoming a reference with minimum required information about wood furniture and wood-based, because it gathers issues that concern the design and manufacturing of furniture, and contributes to the expansion of knowledge on the subject.